The essentials of counselling and psychotherapy in primary schools - Winship, Gary; MacDonald, Shelley (Taylor & Francis, 2018)
The book is targeted at all practitioners in the helping and enabling professions working with children and young people, and is essential reading for anyone undertaking training where elements of psychotherapy and counselling are requisite to practice.